"Seconds save lives – clean your hands": the 5 May 2021 World Health Organization SAVE LIVES: Clean Your Hands campaign. (May 2021) - Allegranzi, B.; Tartari, E.; Pittet, D.
Summary: To highlight the urgent need to save lives by implementing best practices in health care delivery, the slogan for 5 May 2021, world hand hygiene day, is "Seconds save lives – clean your hands". The WHO campaign calls to action key stakeholders: health care workers, IPC practitioners, patients and families, facility managers, policy-makers, vaccinators, and the general public who can play critical roles in achieving optimal hand hygiene at the point of care, helping to strengthen society involvement.